Hubungan Kebiasaan Mencuci Tangan Menggunakan Air Bersih dan Sabun dengan Kejadian Demam Typoid - Naufal Kurniawan , M. Zaidan; Fani, Rif'atul (Jurnal Pustaka Keperawatan (Pusat Akses kajian Keperawatan), 2025)
Typhoid fever is a systemic infectious disease that continues to pose a public health challenge in Indonesia, including Jember Regency. Its transmission is strongly linked to individual hygiene practices, particularly the habit of washing hands with clean water and soap. Although effective handwashing has been proven to reduce the risk of fecal-oral disease transmission, this practice has not been fully adopted as a routine behavior within the community. This study aimed to determine the relationship between handwashing habits using clean water and soap and the incidence of typhoid fever. An observational analytical study with a cross-sectional design was conducted involving 30 respondents selected through purposive sampling based on predefined inclusion criteria. The independent variable was handwashing habits, while the dependent variable was the incidence of typhoid fever obtained from medical records. Univariate analysis was used to describe the frequency distribution, and bivariate analysis was performed using the Chi-Square test with a significance level of 0.05. The results showed that most respondents with poor or moderate handwashing habits experienced typhoid fever (85.7%), whereas those with good habits mostly did not (85.7%). The Chi-Square test indicated a significant relationship between handwashing habits and typhoid fever incidence. The study concludes that proper handwashing using clean water and soap is significantly associated with a lower incidence of typhoid fever. Strengthening health education and promoting clean and healthy living behaviors (PHBS) are essential to reducing the burden of typhoid fever.